Analysis of HOTS Problem Physics of Electrical Static in MA Darussalam Bengkulu City - Dewi Marliani; Istiana Istiana Istiana; Lilis Ageti Dwi Setiawati; Ahmad Ahmad Walid (Jurnal Pembelajaran Fisika, 2019)
This research aims to describe some of the results of the analysis of UN, USBN, and UAS based on Indikatol HOTS and LOTS, knowing how it is developed and how the results of HOTS and LOTS capabilities participants Students at school. As for this type of research that is an observation with the teacher of physic subjects. The subject of this study was a grade XII-MIPA student in the MA Darussalam City of Bengkulu. The results of this observation showed that the percentage of the problem of UN, USBN, and UAS class XII Physics MA school year 2017-2018 in the review of Taksanomi bloom in the revised analysis (C4) in a succession of 86%. 86% and 100%. While the level of evaluating (C-5) is in a row of 14%. 14% and 0%. Problems that have been tested consist of two questions lower-order thinking skills (LOTS) with a percentage of 14.3% and 12 problems HOTS with the problem according to the revision of Bloom's taxonomy is 55.3% level analysis and 21.4% level evaluates. Quality problems in the. Researchers can conclude that the problem of UN, USBN, and UAS who are in the field today is still relatively low to measure HOTS, and problems developed today are enough to have good quality and worth using.